Reflective teaching, inclusive teaching and the teacher's tasks in the inclusive classroom: a literary investigation. (11th April 2019) - Minott, Mark
Abstract : This article has three aims: to continue the process of giving credence to reflective teaching, which is integral to effective teaching and learning; to make explicit the connections between reflective teaching and inclusive teaching; and to identify key tasks for teachers in the inclusive classroom. Relevant articles were selected for inclusion in this review by searching online databases for key words and phrases. Findings reveal that the following features of reflective teaching connect with and are fundamental to inclusive teaching: giving careful consideration or thought; questioning personal assumptions, values, and beliefs; taking initiatives; using intuition; taking part in development and change; and the use of journalling. Teachers' tasks in the inclusive classroom include giving careful consideration to what is to be taught and how it is to be taught (rather than who is to learn); considering the learning needs of all students (not just those with additional needs); questioning beliefs and rejecting deterministic and associated ideas; reflecting on the classroom situation; constantly seeking out and trying new things to support all learners; discussing new initiatives with colleagues in order to receive feedback; examining, framing and attempting to solve dilemmas of the classroom; using journals to track students' learning; and taking responsibility for their own professional growth and understanding.